Chemical composition of the essential oil of Photinia serrulata L. flowers (Bangladesh Journal of Botany, 2019)
The chemical composition of the essential oil of Photinia serrulata L. flowers obtained by hydrodistillation was analyzed by GC/MS for the first time. The major compounds of the oil were found to be benzoic aldehyde (75.2%), docosane (4.0%), phenethyl alcohol (3.0%), pentacosane (1.3%) and benzyl alcohol (1.2%).